2017
DOI: 10.1096/fj.201600878r
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the hypoxia‐inducible factor 1a promotes myogenesis through the noncanonical Wnt pathway, leading to hypertrophic myotubes

Abstract: Regeneration of skeletal muscle is a complex process that requires the activation of quiescent adult stem cells, called satellite cells, which are resident in hypoxic niches in the tissue. Hypoxia has been recognized as a key factor to maintain stem cells in an undifferentiated state. Herein we report that hypoxia plays a fundamental role also in activating myogenesis. In particular, we found that the activation of the hypoxia-inducible factor (HIF)-1α under hypoxia, in murine skeletal myoblasts, leads to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…During muscle repair, the Wnt transcription factor β-catenin (CTNNB1) mediates Wnt target-gene transcriptional regulation during satellite cell, proliferation, differentiation and fusion with myotubes 34 41 . Previous studies have also shown that activation of canonical Wnt signaling was therapeutic in rodent models of muscular dystrophy and acute injury 39 , 42 45 . We examined whether REV-ERB antagonism may also be modulating Notch and Wnt signaling activity in SkM.…”
Section: Resultsmentioning
confidence: 96%
“…During muscle repair, the Wnt transcription factor β-catenin (CTNNB1) mediates Wnt target-gene transcriptional regulation during satellite cell, proliferation, differentiation and fusion with myotubes 34 41 . Previous studies have also shown that activation of canonical Wnt signaling was therapeutic in rodent models of muscular dystrophy and acute injury 39 , 42 45 . We examined whether REV-ERB antagonism may also be modulating Notch and Wnt signaling activity in SkM.…”
Section: Resultsmentioning
confidence: 96%
“…One study showed that HIF-1a promotes stem cell quiescence while downregulating the WNT/b-Catenin pathway and inhibits myogenesis by degrading the early muscle-specific transcription factor MyoD1 (42), whereas another report has indicated that deletion of both HIF-1a and HIF-2a impairs satellite function and, subsequently, skeletal muscle regeneration (43). Furthermore, a very recent study indicated that activation of HIF-1a promotes myogenesis through the noncanonical WNT pathway (57). Our results demonstrated that inactivation of HIF-1a with the inhibitor PX487 during myogenic differentiation of WT and MRL/MpJ MDSPCs led to increase in myotube formation, which is consistent with other reports and suggests an inhibitory role of HIF-1a in myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described (27,28). Experiments were repeated 3 times, and GAPDH expression was used for normalization.…”
Section: Western Blot Analysismentioning
confidence: 99%